Ecological risk assessment in pesticide contamination scenarios: from individuals to ecosystems responses - Sanchez, André Luís (2016)
Ecological risk assessment (ERA) studies are important to assess environmental changes that have been caused by anthropogenic activities. These integration models show the estimation of adverse risk effects across the levels of biological organization potentially exposed to perturbation, including a better understanding of the ecosystems complexity. It is well known that the pesticide have severe environment effects contributing to biodiversity loss and trophic levels changes. In this context, the aim of this study was to evaluate the ecological risk assessment in pesticide contamination scenarios for aquatic and terrestrial compartments. To attempt it direct and indirect effects on individual response for different biological organization and for multi trophic interactions responses with ecosystems models were evaluated. Thus the environmental impacts in relation to losses and changes of the ecosystems functions and services were analyzed. For this purpose, a risk scenario was designed to compare the Ivermectin contamination exposure routes, via dermal (soil) and oral (food) on Eisenia fetida reproduction tests. An experimental approach was constructed to characterise the effects of the fungicide Scala® (Pyrimethanil) in spraying application comparing to homogenous soil application on a constructed soil multi-species test system. n experiment was performed to reported the effects of the fungicide Mythos® (Pyrimethanil) with terrestrial plant test followed by elutriate test with non-targets freshwater organisms and avoidance test with soil invertebrates and quantify the ecosystems services framework. A holistic higher tier fungicide risk assessment was done with terrestrial and aquatic responses and trophic levels with multitrophic interactions in ecosystem models and supplementary with individuals\' responses. The results obtained suggest that the analyzed reproduction parameters for earthworms were affected with the increase of ivermectin concentrations with statistical significant differences between the contamination exposure routes. The fungicide pyrimethanil has adverse effect on soil invertebrates\' response for the application and spatial distribution with the habitat preferences and foraging abilities has affected directly or indirectly by the fungicide toxicity. The impacts by the runoff and leaching pesticides into adjacent water bodies and surrounding soil showed changes in the organism\'s structure with changes and loss in the provisioning, regulatory and supporting services. The integrated holistic four-tiered fungicide risk assessment showed the possible impacts and the adverse effects on the terrestrial and aquatic organisms, ecosystems and processes in the simulate scenarios. From the results, it is possible to conclude that the experiments performed crossed the multiple aspects of contaminations and show the individuals to ecosystems responses approaches using the exposure routes of contamination, multi trophic interactions of experimental ecosystems models, behavioral, individual and some comparatives responses with aquatic and terrestrial compartments in risk assessment. Furthermore, this study are an important register for the deleterious effects and responses to impacts of pesticides, prompting the possible environmental losses and changes of the ecosystems functions and services in disturbances areas.